Validation of the Medical Research Council sum score (MRCss) for use in Russian-speaking patients with chronic inflammatory demyelinating polyneuropathy - N. A. Suponeva; A. S. Arestova; E. A. Melnik; A. A. Zimin; A. B. Zaytsev; A. Yakubu; E. S. Sherbakova; D. G. Yusupova; D. A. Grishina; E. V. Gnedovskaya; M. A. Piradov (Нервно-мышечные болезни, 2023)
Background. The use of rating scales and questionnaires is essential in an evaluation of disease course, treatment response, the disability level and quality of life in patients with chronic inflammatory demyelinating polyneuropathy. The Medical Research Council (MRC) scale and its modification Medical Research Council sum score (MRCss) are widely used for measurement of motor deficit in patients with neuromuscular disorders. However, its usage is limited by the absence of the validated version for Russian-speaking patients.Aim. To validate MRCss scale in patients with chronic inflammatory demyelinating polyneuropathy with development of a Russian version.Materials and methods. We enrolled 50 patients with chronic inflammatory demyelinating polyneuropathy (25 with typical chronic inflammatory demyelinating polyneuropathy and 25 with Lewis–Sumner syndrome). At the first step we conducted linguocultural ratification according to the standard protocol. At the second step the psychometric parameters were evaluated, such as reliability, validity and sensitivity.Results. The developed Russian version of MRCss scale demonstrated the high level of reliability, validity and sensitivity.Conclusion. As a result, we developed a validated Russian version of MRCss scale, recommended for clinical practice and research.